PENGGANDAAN UANG DALAM PERSPEKTIF PASAL 378 KUHP DAN HADITS RIWAYAT IMAM MUSLIM - Angraeni, Muthiara; Arifin, Tajul (al-Rasῑkh: Jurnal Hukum Islam, 2023)
This article analyzes the prohibition of money duplication as stipulated in Article 378 of the Indonesian Criminal Code (Kitab Undang-Undang Hukum Pidana) and the perspective of a hadith narrated by Muslim. The research aims to gain insights into the conception of this prohibition in the context of criminal law and the Islamic religious view. A normative research method is employed, which involves examining available legal sources. The legal sources used include primary legal sources based on Article 378 of the Criminal Code and Islamic legal sources, namely the hadith narrated by Muslim. Secondary legal sources obtained from journals, books, and supporting documents are also utilized. The analysis indicates that Article 378 of the Criminal Code prohibits actions of money duplication involving manipulation or fraud to obtain unlawful profits. This article provides a more comprehensive understanding of the prohibition of money duplication from the perspectives of criminal law and Islam.